Hemodynamic Response of High- and Low-Dose Dexmedetomidine of Pediatric in General Anesthesia: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Josephine, C. (Taiwan Society of Anesthesiologists, 2021)
Dexmedetomidine is a highly selective α2-adrenoceptor agonist, which is off-labelled use for pediatric sedation. However, the hemodynamic responses of dexmedetomidine remain unclear in the pediatric population. The primary objectives of this systematic review and meta-analysis were to examine the hemodynamic effects of high-dose and low-dose dexmedetomidine in pediatric patients undergoing surgery. EMBASE, MEDLINE, and CENTRAL were systematically searched from its inception until April 2019. All randomized clinical trials comparing high-dose (＞ 0.5 mcg/kg) and low-dose (≤ 0.5 mcg/ kg) dexmedetomidine in pediatric surgical patients were included, regardless of the types of surgeries. Observational studies, case series, and case reports were excluded. Four trials (n = 473) were included in this review. Our review demonstrated that high-dose dexmedetomidine was associated with lower heart rate than low-dose dexmedetomidine after intravenous bolus of dexmedetomidine (studies, 3; n = 274; mean difference MD, -5 -6 to -4; P ＜ 0.0001) and during surgical stimulant (studies, 2; n = 153; MD, -11 -13 to -9; P ＜ 0.0001). In comparison to the low-dose dexmedetomidine, high-dose dexmedetomidine was also associated with a significant longer recovery time (studies, 3; n = 257; MD, 5.90 1.56 to 10.23; P = 0.008) but a lower incidence of emergence agitation (studies, 2; n = 153; odds ratio, 0.17 0.03 to 0.95; P = 0.040). In this meta-analysis, low-dose dexmedetomidine demonstrated better hemodynamic stability with shorter recovery time than high-dose dexmedetomidine. However, these findings need to be interpreted with caution due to limited published studies, a small sample size, and a high degree of heterogeneity.